"Cuidado de Enfermería vivenciado por el paciente adulto hospitalizado con quemaduras. Servicio de Cirugía del Hospital Belén de Trujillo- 2013" - Gil Ibañez, Fiorella Isabel (2013)
This qualitative research, phenomenological method will be performed in adult patients hospitalized with burns, the Hospital Belén de Trujillo. For data collection was considered to 7 subjects participants to reach saturation of speeches. According to the results obtained in this investigation, to make the conceptual approach, the adult patient hospitalized with burns states that the care you receive, the nurse conveys various attitudes, which were grouped into two categories: Resonances and Care Care dissonances. Found within these various indicative, the most salient Human Care, Trust, Communication, Kindness, Compliance and Equity of Care Treatment. However the patient experiences changes in your body, in this case study, burns, where going through times when a caregiver needs, as well as needs to be comforted through nursing care, which should include spaces for communication and patient confidence.